2018
DOI: 10.3390/ijerph15112381
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Recovery of Evacuees and Residents from the Fukushima Daiichi Nuclear Power Plant Accident after Seven Years—Contribution of Social Network and a Desirable Lifestyle

Abstract: The 2011 Fukushima nuclear accident resulted in the exposure to radiation and evacuation, which has created psychological distress among the Fukushima residents. With the provision of multi-faceted support and the progress of the reconstruction, their mental health has appeared to show signs of recovery. However, there have been few studies investigating their recovery. To clarify the related factors associated with mental health recovery, a cross-sectional questionnaire survey was conducted. Subjects whose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
1
18
0
1
Order By: Relevance
“…Under the present reconstruction conditions, evacuees can choose to return to their original home in the ex-evacuation area or live in a new location outside of the ex-evacuation area. A previous study reported that 80% of evacuees had recovered their prior mental health status, compared to 84.4% for those who had lived in the non-evacuation area [ 13 ]. Moreover, returnees who have returned to their original home show a significantly better psychological distress status when compared to evacuees [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under the present reconstruction conditions, evacuees can choose to return to their original home in the ex-evacuation area or live in a new location outside of the ex-evacuation area. A previous study reported that 80% of evacuees had recovered their prior mental health status, compared to 84.4% for those who had lived in the non-evacuation area [ 13 ]. Moreover, returnees who have returned to their original home show a significantly better psychological distress status when compared to evacuees [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…During this period, evacuees were forced to make difficult choices of whether to return or not, which increased their psychological burden. The lifting of the evacuation order (over wider areas than before) from March to April 2017 is thought to have triggered a decline in the number of evacuees and a decline in social networks [ 28 ]. These results suggest that when life changes once again after a disaster, such as with the lifting of evacuation orders, it is necessary to screen people at risk of suicide at an early stage and link them to support mechanisms, and long-term follow-up is necessary for women.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies conducted following the Fukushima Daiichi nuclear power plant accident, participating regularly in physical activity was significantly associated with maintaining a healthy mental health status among employees, even in harsh workplace conditions [17]. Moreover, regular physical activity is associated with the promotion of mental health recovery [18]. According to the multivariate analysis, subjective sleep insufficiency and drinking problems 3 years after the accident were associated with the severity of psychological distress [30].…”
Section: Association Between Media Utilization and Lifestyle Variables Related To Health-promoting Activitiesmentioning
confidence: 93%
“…According to previous studies, these variables were associated with residents' mental health status in Fukushima. Therefore, we selected these variables as independent variables in the present study [13,17,18].…”
Section: Lifestyle Variables Related To Health-promoting Activities Following the Accidentmentioning
confidence: 99%